Normative constraints and opportunities for women’s economic resilience to climate change in chicken, cassava and fish value chains of selected sites in Tanzania - Achandi, Esther L.; Bullock, Renee; Galiè, Alessandra; Jeremiah, Adolf; Msita, Sarah; Mwakanyamale, Devis F.; Obuolo, Enoch (CGIAR Initiative on Gender Equality, 2023)
This work was supported by CGIAR’s HER+ research initiative which identifies and tests climate solutions that do work—and work in specific and practical ways—for women as well as men, bringing to the fore evidence of best practices and lessons learned. It was also supported by the CGIAR Initiative on Sustainable Animal Productivity, Nutrition and Gender Inclusion (SAPLING). CGIAR research is supported by contributions to the CGIAR Trust Fund. CGIAR is a global research partnership for a food-secure future dedicated to transforming food, land, and water systems in a climate crisis.